THE EFFECT OF TIME MANAGEMENT AND CORE COMPETENCY ON THE MATHEMATICS LEARNING OUTCOMES OF CLASS VIII - Nita Novianti; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
The average of mathematics learning outcomes in students class VIII of State Junior High School 2 Kasihan (SMP Negeri 2 Kasihan) is below the minimum score. The purpose of this research is to study the influences of time management and interpersonal skill on mathematics learning outcomes in students class VIII of SMP Negeri 2 Kasihan in the odd semester of the 2016/2017 academic year. The population of this research is 135 students of class VIIIA-D of SMP Negeri 2 Kasihan. Random Sampling used to take the sample data, classes B and D are the class sample, and class A is the test class. The instrument used is questionnaires time management, questionnaires interpersonal skills, and mathematic exam cases. Every device being studied through validation tests, rehabilitation tests, and especially discrimination power used to study the mathematic exam case instrument. After all the data being collected, a further study being held through the normality test and homogeneity test. From now on, the hypothetical test being held with the factorial design of 2  2. In the end, the ANAVA test also being conducted through t-test and Least Significant Different (LSD) to compare the highest and lowest average of every instrument. The result of this research is: (1) There is an influence of time management on mathematic learning outcomes in students class VIII of SMP Negeri 2 Kasihan in the odd semester of 2016/2017 academic year with the  is = 9,5073 >  = 3,986 in the 5% significance. (2)  There is an influence of interpersonal skill on mathematic learning outcomes in students class VIII of SMP Negeri 2 Kasihan in the odd semester of 2016/2017 academic year with the  is = 4,6077 ≥  = 3,986 in the 5% significance. (3) There is an influence of time management and interpersonal skill on mathematic learning outcomes in students class VIII of SMP Negeri 2 Kasihan in the odd semester of 2016/2017 academic year with the >  is = 4.0858 ≤   in the 5% significance.